ON THE ISSUE OF THE OFFSHORE AREAS - E. B. Aliyev (Vestnik MGIMO-Universiteta)
Research issue raised in this paper is the most pressing at the moment because of international campaign to prevent money-laundering and tax evasion. From the solution to the problems that will be discussed here may depend the degree of how strong the whole state (country) may become. At the moment there is a legal knowledge gap on this matter caused by the lack of basic scientific research. In the first part of the paper the focus will be made on the definition of the "offshore mechanism" concept which will help to stay objective in further judgments on the phenomenon. Moreover, the author will carefully analyze what reasons push many companies and individuals to use this financial mechanism. In the second part of the paper the author will discuss about the fundamental problems in application of the services from offshore financial centers. Particularly, the author will describe the main application fields of this mechanism and the methods for the tax planning. In addition to that the author will investigate the application of European VAT system, and the ways it can be associated with the application of offshore mechanism under European Union. A special attention will be given to analyzing abuses associated with the usage of the European VAT system. Since only by knowing all these problems in details it will be possible to prevent such mistakes in future.